Pulse Electrodeposition of Palladium Nanoparticles onto Silicon in DMSO - Orest Kuntyi; Mariana Shepida; Oksana Dobrovetska; Stepan Nichkalo; Sergiy Korniy; Yuriy Eliyashevskyy (Journal of Chemistry)
The deposition of palladium nanoparticles (PdNPs) on the surface of n-Si (100) substrate by pulsed electrolysis in dimethyl sulfoxide (DMSO) solutions of Pd(NO3)2 was investigated. It has been shown that nonaqueous medium (DMSO) contributes the Pd (II) recovery at high cathode potential values avoiding side processes to occur. In combination with the pulse mode, this allows the deposition of spherical PdNPs with their uniform distribution on the silicon surface. We established that the main factors influencing the geometry of PdNPs are the value of the cathode potential, the concentration of palladium ions in solution, and the number of pulse-pause cycles. It is shown that with increasing Ecathode value there is a tendency to increase the density of silicon surface filling with nanoparticles. As the concentration of Pd(NO3)2 increases from 1 to 6 mM, the density of silicon surface filling with PdNPs and their average size also increase. We found that with increasing the number of pulse-pause cycles, there is a predominant growth of nanoparticles in diameter, which causes 2D filling of the substrate surface.